Cellulose Nanocrystal Based Chiral Structures for Photonic Applications - Mendes, Bruno Martins (2022)
This thesis documents the fabrication and characterization of flexible ultraviolet (UV) sensors based on cellulose nanocrystals (CNC) as photonic films, for circularly polarized light sensing. The produced films exhibit an inherent left-handed chiral nematic structure which can be used as a filter for CPL in the visible range, where left CPL is reflected and right CPL is transmitted (LCPL and RCPL, respectively), creating a photonic bandgap. This property will be one of the focuses of the final device, allowing the production of specific electronic outputs depending on the polarization of the irradiating light. One of the main objectives of this work is the modulation of the photonic bandgap using potassium hydroxide, allowing for the tuna-bility of the workable spectrum (near-UV to red visible light). The second objective is the im-plementation of the photonic film into a UV sensor capable of distinguishing between R- and LCPL. The sensing layer is a zinc oxide (ZnO) ink with carbon contacts, deposited by screen-printing. The device was then encapsulated between cellulose acetate and characterized. Op-tical characterization shows a blue shift of the photonic bandgap with the addition of potas-sium hydroxide (from 700 nm with no substitutions to 430 nm with 150% substitution) result-ing in a near-linear relation between the photonic bandgap and increasing addition of the hy-droxide without relevant modification in the structure of the crystal. Electrical characterization presents an electronic signal distinction between left and right CPL ranging from 5-15%.